The Effect of Liquidity, Solvency, Profitability, and the Ratio of Market Valuation to Stock Return on Property and Real Estate Sector Companies Listed on The Indonesia Stock Exchange for the 2017-2022 Period - Deasy Putri Avanda Sari; Achmad Hizazi; Salman Jumaili (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to determine how much stock returns are influenced by liquidity, solvency, profitability, and market valuation ratios. The population of this research is property and real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The sample used in this research amounted to 44 companies. The analytical method used was multiple linear regression analysis using IBM SPSS version 25 program. The results showed that simultaneously liquidity, solvency, profitability, and market valuation ratios affect stock returns with an adjusted R2 value of 0.032 or 3.2% (very weak). Liquidity partially affects stock returns. While solvency, profitability, and market valuation ratios have no effect on stock returns